The effect of fibre intervention on serum and faecal short-chain fatty acids in human with overweight or obesity: a systematic review of human intervention studies - Rinta Amalia; Etika R Noer; Diana N Afifah; Andri C Kumoro; Adriyan Pramono; Muflihatul Muniroh (Journal of Biomedicine and Translational Research, 2022)
Overweight/ obesity is associated with cardiovascular diseases, which both contribute to the severity of coronavirus disease 2019 (COVID-19). Nutritional interventions focusing on dietary fibre and prebiotics interventions have been implemented. Fibre has been suggested to modulate gut-derived metabolites short-chain fatty acid (SCFA). We conducted a systematic review on fibre (including prebiotics) interventions to depict its effect on SCFA from faecal and blood using standard methodologies. PubMed, Cochrane, Embase, CINAHL, and Scopus databases were systematically searched to yield peer-reviewed articles published until 31 December 2021. We included 17 articles describing fibre (including prebiotics) intervention in adult individuals with overweight/obesity. These interventions were broadly described into 3 groups: (i) fibre type food items (n = 8); (ii) fibre supplementations (i.e. prebiotics) (n = 8); (iii) prebiotic supplementation combined with CRD (n = 1). Fibre type food items intervention mostly affected the changes of acetate in faecal, whilst propionate mostly changed in the blood. Interestingly, intervention with fibre supplementation affects more the increase of faecal and blood acetate. Furthermore, fibre intervention might have an impact on the gut microbiota. Nevertheless, more well-controlled human studies are needed, with a more personalized approach.